FVS-TECHNOLOGY: INTELLECTUAL SEARCH TOOLS - MUMINOV, BAHODIR; Bekmurodov, Ulugbek (IIUM Engineering Journal, 2020)
It is enough to have 3 basic stages of the modules in the SPD of a diversified corporate network: (F) - the method of submitting the request, i.e. the method of forming the expression of the information needs of the system user (S) - the function of the correspondence of the electronic resource to the request degree of compliance with the request and the found electronic resource; (V) - method of presenting electronic resources. Combining these three stages for models, methods, and software modules of the AML, is referred to as FSV technology (FSV platform, FSV Framework). FSV technology is an instrumental software platform based on a client-server architecture, integration and modification of models, and methods and algorithms of AML in the information environment of corporate networks. The following architecture has been developed for the FSV technology proposed for the search index in data retrieval systems. ABSTRAK: Tiga peringkat asas modul adalah cukup dalam pelbagai rangkaian korporat SPD iaitu: (F) - kaedah penyerahan permintaan, kaedah membentuk ungkapan keperluan maklumat pengguna sistem (S) - fungsi surat-menyurat sumber elektronik bagi permintaan tahap pematuhan permintaan dan sumber elektronik yang dijumpai; (V) - kaedah penyampaian sumber elektronik. Gabungan tiga peringkat model, kaedah dan modul perisian AML, dipanggil teknologi FSV (platform FSV, rangka FSV). Teknologi FSV adalah platform perisian instrumen berdasarkan seni bina pelanggan-pelayan, integrasi dan pengubah suaian model, kaedah-kaedah dan algoritma AML dalam persekitaran maklumat dalam rangkaian korporat. Seni bina ini telah di bina bagi teknologi FSV yang dicadangkan bagi indeks carian dalam sistem dapatan data.